Budidaya dan desain kumbung untuk meningkatkan produksi jamur tiram putih (Pleurotus ostreatus) - Elin Nurlina; Putranti Adirestuti; Ahmad Marjan; Endang Rosdiana; Asep Hodijat; Ate Romli (Jurnal Abmas, 2014)
Cultivation of oyster mushroom (Pleurotus ostreatus) provide business opportunities for mushroom farmers' groups, such as in the area of West Bandung regency Cisarua, because the region is cool temperate with the weather tends to be moist, but the farmer groups often face problems in their business. The results of the survey are gathering location problems in mushroom cultivation, suggesting that the lack of facilities and infrastructure to support a cause of the problem. Devices complementary tool in kumbung mold and mildew breeding facilities is the biggest obstacle, so generally the rainy season oyster mushroom production was down to 70 %. Efforts have been made to help resolve these problems is training in the form of images and movie demonstration of good farming techniques, a visit to some of the groups that have experienced mushroom growers, alternative cultivation, mushroom spawn preparation techniques and design tools that can regulate the temperature and humidity conditions kumbung room in the house. The instrument is made to the model introduced simple technology that is easy to manufacture, easy to use and inexpensive in financing.